Dasar Hukum Penataan Lembaga negara yang tidak Diatur Undang-Undang Dassar Negara Republik Indonesia - Harimurti, Yudi Widagdo (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2019)
This study aims to explain the occurrence of various types of rules as the legal basis for regulating state institutions that are not regulated by the 1945 Constitution of the Republic of Indonesia and the types of rules that are appropriate for the legal basis for regulating state institutions that are not regulated by the 1945 Constitution. The study shows that the problems in structuring state institutions are due to the absence of a common legal basis for state institutions that are not regulated by the 1945 Constitution of the Republic of Indonesia. The types of rules that are appropriate as the legal basis for regulating state institutions that are not regulated by the 1945 Constitution of the Republic of Indonesia are the laws.